Thomas Erastus and the Palatinate A Renaissance Physician in the Second Reformation - Gunnoe, Charles D. (Brill's Series in Church History, 2010)
Utilizing Erastus's correspondence, this book offers a synthetic treatment of Erastus's career in the Palatinate including his role in the territory's conversion, the Heidelberg Catechism, the church discipline controversy, as well as his refutation of Paracelsus and Johann Weyer. Readership: All those interested in intellectual history, Reformed Protestantism, Calvinism, the Second Reformation, the Heidelberg Catechism, church discipline, church and state in early modern Europe, Erastianism, Paracelsianism, Renaissance medicine, demonology, and witchcraft.